Optimalisasi Acid Cleaning Pada Cell Generator Chlorination Plant Dengan Menggunakan Acuan Tegangan - Ammar Asof; Nurmiati Pasra; Gilang Yuri Wibowo (JURNAL POWERPLANT, 2015)
Sea water contains a lot of marine life. If the growth is not inhibited marine life, it can be attached to the installation path (biofouling). Later, as a result of this biofouling will reduce the efficiency of installations through which sea water tersebu t and will add to the cost of production units. Chemical liquid sodium hypochlorite (NaOCl) produced by chlorination plant breeding serves as a barrier to marine organisms. This fluid is produced in the chlorine generator cell through a process of electrolysis of seawater. In fact, electrolysis of sea water also produce side reactions. Namely the deposition of minerals such as magnesium (Mg) and calcium (Ca). As a result, the cell voltage chlorine generator will increase in the use of the same current. Therefore, it is necessary that the process of cleaning acid cell kembalibersih chlorine generator. Reference implementation of the process of cleaning acid that is based on the operating time and based on the voltage. Commissioning of the data, has been conducted several times a dry acid process based on the operating time of 250 H / ± 10 days. But the acid cleaning process is inefficient and ineffective. Therefore, the new reference is made in the implementation process of cleaning acid, wherein the voltage value menjad iacuannya. Several advantages, including the total cost of implementing the dry acid in cycle 1 (one) month more efficient, improve the efficiency and effectiveness of cleaning acid and time flexibility in the implementation process of cleaning acid.